Skeletal malformation of fetuses from pregnant Sprague Dawley rats fed Jatropha curcas crude oil (JCO) - Abdul Mutalib, Noor Haziyah; Samat, Yon Thannia; Sukardi, Sabrina (Centre for Enhancing Knowledge, 2014)
Studies on the teratogenicity effects of Jatropha curcas has been reported in pregnant rats. This study was conducted to observe whether feeding Jatropha curcas seeds crude oil (JCO)to pregnant rats during early and late gestation will cause fetal skeletal malformations. A hundred sexually mature female rats were divided equally into 2 groups: early and late gestation. Each group was then subdivided equally into 5 groups: positive control (retinylpalmitate), vehicle control (corn oil), low dose (0.175ml/kg), medium dose (0.35ml/kg) and high dose (0.7ml/kg) of JCO. Rats were mated overnight and positive pregnant ratswere treated on days 1-7 (early group) and days 8-14 (late group). Rats were sacrificed on day 21 of pregnancy. Fetuses were processed accordingly and any skeletal malformations were recorded. Data show fetuses in high treatment group were significantly smaller as compared to other groups. Skeletal abnormalities in fetuses from all JCO treated groups were observed suggesting fetotoxicity.